1995
DOI: 10.1089/end.1995.9.59
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cystectomy and Ileal Conduit: Case Report

Abstract: A completely new combined laparoscopic cystectomy and ileal conduit technique for removal of an infiltrating bladder cancer was carried out on a 64-year-old woman. The bladder was dissected free and extracted whole through the right flank. The right ureter and a loop of intestine were withdrawn through the same incision. An ileal segment was isolated and intestinal continuity restored. The right ureter was anastomosed to one extreme of the segment that was then reintroduced into the abdomen, taken across to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(71 citation statements)
references
References 2 publications
0
63
0
8
Order By: Relevance
“…Three patients with stage T3aN0M0, T3aN1M0 and T3bN1M0 were receiving adjuvant chemotherapy. Mean follow up was 6.1 months (range [4][5][6][7][8][9][10][11][12][13][14] and all patients have normal renal function. No metastases have been detected and all are alive and free of disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three patients with stage T3aN0M0, T3aN1M0 and T3bN1M0 were receiving adjuvant chemotherapy. Mean follow up was 6.1 months (range [4][5][6][7][8][9][10][11][12][13][14] and all patients have normal renal function. No metastases have been detected and all are alive and free of disease.…”
Section: Resultsmentioning
confidence: 99%
“…in 1993. 12 Since then, LRC have been confined to a few centers in the world because it is a technically demanding procedure. The pelvic cavity is limited and there are complex vascular structures surrounding the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of the ileal loop and ureteral re-implantation through an extended 3 cm port site incision has inherent problems such as tissue orientation that could potentially lead to positional distortion. Moreover, it may be difficult or even impossible to extract the ileum and the ureters to the skin level in obese patients (12,13).…”
Section: Commentsmentioning
confidence: 99%
“…In another case, Sanchez de Badajoz et al [50] reported the ®rst laparoscopic radical cystectomy with ileal conduit diversion in a patient with invasive bladder cancer. No data were available from this report on the length of hospital stay, operating time or complications after surgery.…”
Section: Laparoscopic Radical Cystectomymentioning
confidence: 99%